Long-term outcomes with nonmyeloablative HLA-identical related HCT using tacrolimus and MMF for GVHD prophylaxis - Oshima, Masumi Ueda (Transplant Cell Ther, 2020)
Nonmyeloablative allogeneic hematopoietic cell transplantation (HCT) from HLA-identical related donors using cyclosporine (CSP) and mycophenolate mofetil (MMF) for post-grafting immunosuppression is effective therapy for hematologic cancers. However, graft-vs-host-disease (GVHD) remains a major cause of morbidity and mortality. Pilot data suggested lower acute GVHD incidence with tacrolimus/MMF compared to historical experience using CSP/MMF after nonmyeloablative HCT. In a phase II multicenter trial, we evaluated the effect of tacrolimus/MMF for GVHD prophylaxis after HLA-identical related donor peripheral blood HCT in patients with hematologic malignancies (n=150) using conditioning with 2 Gy total body irradiation (TBI) for patients with a preceding (within 6 months) planned autologous HCT (n=50), or combined with 90mg/m(2) fludarabine for those without recent autologous HCT (n=100). Oral tacrolimus was given from days −3 to 56 (tapered by day +180 if no GVHD). Oral MMF was given from days 0 to 27. Patient median age was 57 (range 20–74) years. The cumulative incidences (CI) of day-100 grade II-IV and III-IV acute GVHD were 27% and 4%, respectively. With median follow-up of 10.3 (range, 3.1–14.5) years, the 5-year CI of chronic extensive GVHD was 48%. One and 5-year estimates of non-relapse mortality, relapse/progression, survival, and progression-free survival were 9% and 13%, 35% and 50%, 73% and 53%, and 56% and 37%, respectively. GVHD prophylaxis with tacrolimus/MMF resulted in a low risk of acute GVHD and compared favorably with results from a concurrent trial using CSP/MMF. A randomized phase III trial to investigate tacrolimus/MMF versus CSP/MMF in nonmyeloablative HCT is warranted.